Understanding Telegram User Continuance: Extending the ECM with Trust and Perceived Risk - Aryaguna, Arvin; Oktavia, Tanty (International Journal of Electronics and Communications Systems, 2026)
Sustaining user engagement has become a critical challenge for encrypted instant messaging platforms, where continued usage depends not only on functional performance but also on users’ perceptions of trust and security. This study examines the determinants of Telegram continuance intention in Indonesia by extending the Expectancy-Confirmation Model (ECM) with trust and perceived risk. A quantitative survey was conducted among 410 active Telegram users with at least three months of experience, and the proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings confirm that expectation confirmation enhances both perceived usefulness and user satisfaction, while satisfaction emerges as the strongest determinant of continuance intention. Trust also plays a pivotal role by directly strengthening satisfaction and users’ intention to continue using Telegram. Interestingly, higher trust is associated with greater awareness of potential risks, revealing a trust–risk paradox in highly encrypted communication platforms. However, perceived risk does not directly discourage continued use, suggesting that strong trust can offset the negative influence of perceived security concerns. In addition, perceived usefulness no longer directly predicts continuance intention, indicating that functional benefits have become baseline expectations on mature messaging platforms. This study extends the ECM by demonstrating that long-term user retention is primarily driven by the interplay between trust and satisfaction rather than functional usefulness alone, offering practical implications for designing trust-centered communication platforms.